Development of a Remote Handling System in an Integrated Pyroprocessing Facility. (9th October 2013) - Lee, Hyo Jik; Lee, Jong Kwang; Park, Byung Suk; Kim, Kiho; Ko, Won Il; Cho, Il Je
Over the course of a decade-long research programme, the Korea Atomic Energy Research Institute (KAERI) has developed several remote handling systems for use in pyroprocessing research facilities. These systems are now used successfully for the operation and maintenance of processing equipment. The most recent remote handling system is the bridge-transported dual arm servo-manipulator system (BDSM), which is used for remote operation at the world's largest pyroprocess integrated inactive demonstration facility (PRIDE). Accurate and reliable servo-control is the basic requirement for the BDSM to accomplish any given tasks successfully in a hotcell environment. To achieve this end, the hardware and software of a digital signal processor-based remote control system were fully custom-developed and implemented to control the BDSM. To reduce the residual vibration of the BDSM, several input profiles, including input shaping, were carefully chosen and evaluated. Furthermore, a time delay controller was employed to achieve good tracking performance and systematic gain tuning. The experimental results demonstrate that the applied control algorithms are more effective than conventional approaches. The BDSM successfully completed its performance tests at a mock-up and was installed at PRIDE for real-world operation. The remote handling system at KAERI is expected to advance the actualization of pyroprocessing.